PERAN REMAJA MASJID DALAM MENGEMBANGKAN KARAKTER RELIGIUS DAN SOSIAL MASYARAKAT (Studi Kasus Remaja Masjid An-Nur Desa Waikafa, Kecamatan Mongoli Selatan, Kabupaten Kepulauan Sula) - Fataruba, Ardila; Noe, Wahyudin; Abbas, Irwan (Universitas Khairun, 2024)
Mosque youth as the nation's successors play an important role in driving change in society through spiritual and social activities. This is what happened to the youth of the An-Nur Waikafa Mosque, South Mongoli, Sula Islands, who were successful in holding activities that directly touched the residents to increase the value of spiritual and social worship, even though they faced various challenges, such as some teenagers who were indifferent, lazy, and more tend to exhibit hedonic relationships. This research is qualitative research with a case study type using data collection techniques such as observation, interviews and documentation studies, while data analysis techniques are data reduction, data presentation, verification and drawing conclusions. The results of this research are: 1) The role of teenagers at the An-Nur Waikafa mosque in developing religious and social character such as: a) holding regular religious studies, b) fostering TPA (al-Qur’an Education Park) for children, and c) initiating the community involved in social service activities; 2) Supporting factors for the role of mosque youth are: a) the high enthusiasm of residents in participating in the success of activities held by mosque youth, and b) habituation to the culture of religious discussion among teenagers which has been established for a long time. The factors inhibiting the role of mosque youth include: a) the lack of enthusiasm among some teenagers to get involved due to the encouragement of a lazy, indifferent attitude and a more hedonistic style, b) lack of support from residents in the form of financial assistance to make the mosque prosperous.